Mood by microbe: towards clinical translation. Issue 1 (December 2016) - Dinan, Timothy; Cryan, John
Abstract There is a growing realization that the gut–brain axis plays a key role in maintaining brain health and the stress response. Recently, the gut microbiota has emerged as a master regulator of this axis. Thus, opportunities to exploit the microbiome to treat stress-related psychiatric disorders are materializing. Clinical validation of such strategies is now warranted.